Analysis of Husband Support and Behavior of Puerperal Mothers in Using Postpartum Birth Control in the West Range District of Asahan Regency - Dini Tria Anggraini; Putra Apriadi Siregar (International Archives of Medical Sciences and Public Health, 2022)
Postpartum is an effort to prevent pregnancy by using contraception after delivery for up to 42 days. The use of post-delivery family planning in Kisaran Barat District in 2020 is very low, namely 27 participants (22.9%) of 118 postpartum mothers (77.1%), thus increasing the population by 62,121 people. This study aims to determine the husband's support and the postpartum mother's behaviour in postnatal family planning. The researcher uses a qualitative method with a case study approach. Data collection was carried out by in-depth interviews and tested by triangulation to check data: informants eight postpartum mothers and husbands, one religious leader, and one community leader. The research location is in Kisaran Barat District, Asahan Regency, from December 2020 - July 2021. The results show that the knowledge and attitudes of postpartum mothers regarding postnatal family planning have been declared good, but the attitude of husbands who do not support their wives is the biggest obstacle for postpartum mothers not to use Birth control after delivery. For PPBKD officers in Asahan Regency, it is hoped that they will be more intense in conveying counselling to husbands about the importance of postnatal family planning.